Penyusunan Rencana Kerja dan Anggaran Sekolah (RKAS) Berbasis Kebutuhan di Sekolah Dasar - Meti Wigiyantini; Maman Suryaman (PGSD Universitas Muhammadiyah Cirebon, 2025)
The preparation of the School Work and Budget Plan at the primary school level is an important instrument in supporting the achievement of national education goals. This article aims to analyze the importance of preparing RKAS based on the actual needs of students and the challenges faced in its implementation. This research uses a literature study method with a descriptive analytical approach through a review of various literature sources, education regulations, and previous research results. The results showed that more than 60% of primary schools still prepare RKAS by copying the previous year's budget pattern without considering the development of students' needs and curriculum dynamics. This condition creates a gap between the needs-based planning principles mandated in the policy and the practices that occur in the field. This article recommends increasing the capacity of school principals through training in needs analysis-based RKAS preparation, strengthening monitoring and evaluation of budget implementation, and optimizing school community participation with the support of simple technology. With more data-based planning and real needs, RKAS can become a strategic instrument to improve the quality of learning and primary school management in a sustainable manner.